(untitled) (Raparin Journal of Humanities (RJH), 2024)
The goal of this study was to find out how the mutual teaching method affected the reading skills of fifth graders in Erbil Governorate. The experimental method used in the study was to look at how the independent variable affected the dependent variable by gathering data and using the right statistics analysis to get the results. The study population was all fifth-graders in Erbil Governorate who were learning reading in Arabic during the 2022–2023 school year. To make sure the study tool was valid and reliable statistically, an exploratory sample of 35 female students was chosen. The study sample was split into two groups: an experimental group with 33 students studying Arabic reading using the reciprocal teaching strategy and a control group with 33 students studying Arabic reading using traditional teaching methods. The study found that students in the experimental group got better at reading Arabic after receiving and giving lessons back and forth. This is a statistically significant result, which means that the students in the experimental group did better. As they used strategies that helped them understand what they were reading and became more aware of it, like the question the student asks, his explanations of words and structures they didn’t understand, his guesses about what might happen in the text, his reading of the picture that went with the text, and his summary of the text he asked about and his predictions about what would happen in it. All of this makes him more aware of the texts.